Pengaruh Etnosentrisme dan Partisipasi Pelanggan terhadap Intensi Membeli Produk Skincare Korea - Alicia, Celyn; Phoebe, Phoebe; Wibowo, A.J. Ibnu; Ali, Alavi (Universitas Prasetiya Mulya, 2025)
This research aims to investigate the influence of ethnocentrism and consumer participation on the purchase intention towards Korean skincare brands in Indonesia. This study also explores the mediating role of product image in influencing purchase intention. Thus, the research seeks to explore the relationships between variables that have often been studied separately. The research method involves analyzing survey data from 300 respondents, with data collection conducted through Google Forms. To analyze the respondents' data, this study uses SPSS and SEM AMOS software. The results show that three hypotheses are accepted: the relationship between product image and consumer participation, the relationship between product image and purchase intention, and the relationship between consumer participation and purchase intention.